When to intervene and take a stand: Evaluating bystander roles in intergroup name‐calling contexts. (14th December 2022) - Palmer, Sally B.; Hitti, Aline; Abrams, Dominic; Cameron, Lindsey; Sims, Riley N.; Woodward, Bonnie; Killen, Melanie
Abstract: Children ( n = 121, M = 9.86 years, SD = 0.64) and adolescents ( n = 101, M = 12.84 years, SD = 0.69) evaluated proactive and passive bystander behaviour to intergroup name‐calling ( N = 222, 54% female). Scenarios depicted ingroup perpetrators and outgroup victims who were from a stigmatized group (ethnicity) or a non‐stigmatized group (school affiliation), with bystanders depicted as being proactive (intervening to help) or passive (failing to challenge the aggression), counter to their own group's norm. Children and adolescents personally evaluated proactive bystanders more favourably than passive bystanders. However, adolescents, more than children, expected their peers to be more positive about proactive bystanders than passive bystanders in the stigmatized context. Results are discussed in terms of the complexities of bystander decisions and implications for anti‐bullying interventions.